Pili Torti as a Sign of Eyebrow Involvement in Frontal Fibrosing Alopecia - Ferrari, Bruno (Skin Appendage Disord, 2019)
Frontal fibrosing alopecia (FFA) is a disease characterized by progressive band-like scarring alopecia involving the frontotemporal hairline and eyebrow hair loss. It affects mainly postmenopausal women. Trichoscopy features of FFA include absence of vellus hair, perifollicular erythema and scaling (peripilar casts), and absence of follicular openings. Trichoscopy of eyebrows in FFA patients shows tapered and broken hair, absence of follicular openings, black dots, and hair growing in different directions. We report a case of FFA with numerous pili torti in the eyebrows.